Effect of Pulmonary Rehabilitation for Patients With Post-COVID-19: A Systematic Review and Meta-Analysis - Chen, Huan; Shi, Hangyu; Liu, Xitong; Sun, Tianheng; Wu, Jiani; Liu, Zhishun (Frontiers in Medicine, 2022)
Background Evidence increasingly suggested that impaired respiratory function remained in about 40% of patients with coronavirus disease 2019 (COVID-19) after discharge, jeopardizing their activities of daily living and quality of life (QoL) in a long term. Pulmonary rehabilitation (PR) can improve exercise capacity and QoL in individuals with chronic lung disease; however, evidence on the effect of PR for patients with post-COIVD-19 was scarce. This study aimed to conduct a systematic review and meta-analysis to evaluate the effect of PR on lung impairment for patients with post-COVID-19. Methods Five databases were searched for all the published trials of PR for patients with post-COVID-19 from 2019 to October 2021. Data were extracted using a standardized form. The risks of bias of included studies were assessed using the Cochrane risk of the bias assessment tool. Data were synthesized where possible; otherwise, qualitative analysis was done. Results Among 6,000 retrieved studies, 3 studies with 233 patients after COVID-19 were included. The pooled estimate of PR effect on 6-min walk test (6-MWT) (50.41, 95% CI 34.34 to 66.48; p < 0.0001) was in favor of the experiment group with clinical importance. It is found that PR could improve the symptom of dyspnea and QoL; however, its effect on pulmonary function test was inconsistent across studies. The risk of bias of included studies varied, with major concerns on the risk of blinding of participants and interventions performers. Conclusion The review showed that PR could improve exercise capacity measured by 6-MWT among patients with mild-to-moderate lung impairment after COVID-19. The interpretation of effects on lung function, dyspnea, and QoL should be cautious due to inadequate and conflicting data reported across studies. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021289562, identifier: CRD42021289562.